2017
DOI: 10.1101/231738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trait paranoia shapes inter-subject synchrony in brain activity during an ambiguous social narrative

Abstract: 15Individuals often interpret the same event in different ways. How do personality traits modulate 16 patterns of brain activity evoked by a complex stimulus? Participants listened to a narrative 17 during functional MRI describing a deliberately ambiguous social scenario, designed such that 18 some individuals would find it highly suspicious, while others less so. Using inter-subject 19 correlation analysis, we identified several brain areas that were differentially synchronized 20 during listening between pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 57 publications
9
59
0
Order By: Relevance
“…One such relationship was identified by Kaufmann and colleagues, who reported that while adolescents with increased overall psychiatric symptom severity exhibited decreased resting-state connectome distinctiveness compared to healthy individuals, no significant relationship between these variables was found in children (23). Although the association between functional brain typicality and symptom severity was negative in our analyses, we note that functional typicality has been shown to scale positively with some clinically relevant features (trait paranoia (59)) and negatively with others (depression (36) and autism (60) symptom severity). Therefore, while functional typicality appears to serve as an index of psychopathology that emerges during adolescence, future work should clarify how these relationships may differ across psychiatric diagnoses and analytic approaches.…”
Section: Discussionsupporting
confidence: 37%
“…One such relationship was identified by Kaufmann and colleagues, who reported that while adolescents with increased overall psychiatric symptom severity exhibited decreased resting-state connectome distinctiveness compared to healthy individuals, no significant relationship between these variables was found in children (23). Although the association between functional brain typicality and symptom severity was negative in our analyses, we note that functional typicality has been shown to scale positively with some clinically relevant features (trait paranoia (59)) and negatively with others (depression (36) and autism (60) symptom severity). Therefore, while functional typicality appears to serve as an index of psychopathology that emerges during adolescence, future work should clarify how these relationships may differ across psychiatric diagnoses and analytic approaches.…”
Section: Discussionsupporting
confidence: 37%
“…Functional neuroimaging studies have used naturalistic, narrative stimuli to examine how we perceive 11,12 and remember 13 structured events based on memory of contexts, [14][15][16] prior knowledge or beliefs, [17][18][19] and emotional and social reasoning. [20][21][22] However, strikingly few neuroimaging studies have directly probed attention during naturalistic paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Their corresponding effectsb 1k andb 2k are presumably equal, but in the same vein as the practical implementation of subject-specific effects through two separate random-effects components as previously elaborated, the two fixed-effects components ofb 1k andb 2k that are associated with the explanatory variable x would also have to be estimated separately through data duplication. The situation with more than one explanatory variable would be similar except for an expanded form, and this modeling strategy has been applied at the whole-brain voxel level to a few studies in the literature (e.g., Moraczewski et al, 2018;Finn et al, 2018).…”
Section: Isc Analysis With Univariate Linear Mixed-effects Modelingmentioning
confidence: 99%
“…It has been argued that, under a context closer to natural environment, neural responses are more reproducible and reliable than traditional simple repetitive stimuli (Hasson et al, 2010) due to the involvement of extensive cognitive processing (such as working memory, judgment, reasoning, social cognition, etc.). Its adoption has been steadily growing in investigating various aspects of brain functions such as music imagery (Zhang et al, 2017), early childhood development (Moraczewski et al, 2018), personality traits (Finn et al, 2018) and cognitive differences between schizophrenics and controls. For typical task-related designs, the focus is usually on identifying regions activated by an explicit task or condition.…”
Section: Introductionmentioning
confidence: 99%